The Impact of Banking Development on the Size of the Shadow Economy in the Context of Globalization - Tran Thi Kim, Oanh; Nguyen Thi My, Huyen; Ngo Chan, Hung; Nguyen Hau Thanh, Van (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2024)
This study examines the impact of banking development on the size of the shadow economy in the context of globalization during the period 2009–2021 across 34 countries worldwide. Using Bayesian regression and GMM methods, the results indicate that the scale of the shadow economy is inversely correlated with globalization and negatively associated with banking development. This suggests that banking development has a significant negative impact on the size of the shadow economy in countries under the current context of globalization. Based on these findings, the paper offers several policy recommendations for different groups of countries.
Keywords: Shadow economy; Banking development; Globalization; Bayesian; GMM